Increased PD‐L1 Expression in Human Skin Acutely and Chronically Exposed to UV Irradiation. (10th March 2021) - Dickinson, Sally E.; Khawam, Maria; Kirschnerova, Viktoria; Vaishampayan, Prajakta; Centuori, Sara M.; Saboda, Kathylynn; Calvert, Valerie S.; Petricoin, Emanuel F.; Curiel‐Lewandrowski, Clara
Abstract: Overexpression of PD‐L1 (CD274) on tumor cells may represent a hallmark of immune evasion, and overexpression has been documented in several tumors including cutaneous squamous cell carcinoma (cSCC). While PD‐L1/PD‐1 activity in the skin has been primarily described in inflammatory models, our goal was to examine PD‐L1 expression in human keratinocytes exposed to UV irradiation. We assessed PD‐L1 expression in human sun‐protected (SP) and sun‐damaged (SD) skin, actinic keratosis (AK), and cSCC using IHC and protein microarray. Both methods found low baseline levels of PD‐L1 in SP and SD skin and significantly increased expression in cSCC. Next, we examined PD‐L1 expression in acute models of UV exposure. In human SP skin exposed to 2‐3 MED of UV ( n = 20), epidermal PD‐L1 was induced in 70% of subjects after 24 h ( P = 0.0001). SKH‐1 mice exposed to acute UV also showed significant epidermal PD‐L1 induction at 16, 24 and 48 h. A time‐ and dose‐dependent induction of PD‐L1 was confirmed in cultured human keratinocytes after UV, which was markedly reduced in the presence of MEK/ERK, JNK or STAT3 inhibitors. These findings suggest that UV induces upregulation of PD‐L1 through established, pharmacologically targetable stress‐signaling pathways in keratinocytes. Abstract : Programmed death‐ligand 1 (PD‐L1, also known as CD274) expression in normal human epidermis is normally low, but is induced by acute exposure to ultraviolet solar‐simulated light (SSL), as shown in IHC from serial biopsies from the same individual (A). Matched samples from 20 individuals exposed to 2‐3 MED of SSL show significant induction of PD‐L1 in the epidermis at 24 h posttreatment (B). This response is reproduced in mouse models (not shown) as well as in human HaCaT keratinocytes in culture exposed to SSL (C).